VOICING LIBERATION OF WOMEN: QASIM AMIN AND ASMA BARLAS - Andi, Azhari (UIN Raden Mas Said Surakarta, 2024)
Does Islam advocate inequality? This question has been a concern of Muslim scholars in recent centuries, notably Qasim Amin and Asma Barlas. Hence, this paper aims to make a comparative study of Amin and Barlas’s thoughts on the liberation of women. The data will be analyzed through a descriptive-analytic approach. The analysis finds that Amin and Barlas have similarities and differences in voicing women's freedom. They criticize and reconstruct some concepts considered established within the Islamic tradition, such as hijāb and polygamy. They firmly oppose the established idea of hijab, which means covering women's entire bodies except for their eyes, which is contrary to Islamic teaching. They disagree, however, on which a hijab should cover parts of a woman's body. Furthermore, Amin broadens the definition of hijāb, which restricts women's movements (qasr al-mar’ah fī al-bait). In terms of polygamy, however, they critically assessed the classical understanding of the permissibility of polygamy. Therefore, they impose strict conditions on the permissibility of polygamy. Nevertheless, Amin seems to advocate that polygamy is not permissible. Amin and Barlas were inspired to reform Muslim society, specifically women's liberation, by their social context and experiences. Despite their good intentions, their ideas have received both criticism and praise. This mixed reception emphasizes the continuous struggle in the Muslim world about gender, tradition, and modernization.